3, 5-Nonadiyne Rich Accession of Selinum tenuifolium Wall. from Dayara, Uttarakhand, Himalaya. Issue 3 (4th May 2017) - Chauhan, Rajendra S.; Nautiyal, M.C.; Bahuguna, Y.M.; Figueredo, Gilles; Chalard, Pierre
Abstract: Selinum tenuifolium (Apiaceae) is a perennial aromatic herb, growing in humus rich mountain slopes. Underground parts were extracted for the essential oil by using Clevenger-type apparatus and analyzed. Total twenty two constituents composed of 97.64 % of the essential oil were identified. 3, 5-Nonadiyne (a polyacetylenic compound) was major constituent (94.32 %) of the essential oil. p -Methyl anisole and Z -β-ocimene are not reported so far from this species. Chemical composition of 3, 5-nonadiyne rich accession is presented in detail. Characterization of 3, 5-nonadiyne rich accession will opens new avenues for pharmacological, agricultural and industrial sector.